2018
DOI: 10.1038/s41423-018-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating B cells: their role and application in anti-tumor immunity in lung cancer

Abstract: Evidence indicates that lung cancer development is a complex process that involves interactions between tumor cells, stromal fibroblasts, and immune cells. Tumor-infiltrating immune cells play a significant role in the promotion or inhibition of tumor growth. As an integral component of the tumor microenvironment, tumor-infiltrating B lymphocytes (TIBs) exist in all stages of cancer and play important roles in shaping tumor development. Here, we review recent clinical and preclinical studies that outline the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
289
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(297 citation statements)
references
References 93 publications
8
289
0
Order By: Relevance
“…b ). A pervious study reported that B cells could be stimulated by tumor cells and then release growth factors to facilitate tumor growth . Here we examined whether lymphocytes cocultured with HNSCC cells could secrete more LT‐α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b ). A pervious study reported that B cells could be stimulated by tumor cells and then release growth factors to facilitate tumor growth . Here we examined whether lymphocytes cocultured with HNSCC cells could secrete more LT‐α.…”
Section: Resultsmentioning
confidence: 99%
“…A pervious study reported that B cells could be stimulated by tumor cells and then release growth factors to facilitate tumor growth. 27 Here we examined whether lymphocytes cocultured with HNSCC cells could secrete more LT-α. To this end, freshly isolated lymphocytes from the peripheral blood of healthy donors were cocultured with the human HNSCC cell line Cal27.…”
Section: Infiltrated Lymphocytes In Hnscc Secret Lymphotoxin-αmentioning
confidence: 99%
“…These findings suggest that CLEC3B may play an important role in immune infiltration of SCC. The correlations between CLEC3B and immune markers of immune cells (selected by investigating some relevant papers [27][28][29][30][31]) were analyzed in the TIMER database to explore the relationship between CLEC3B and immune infiltrating cells of ADC and SCC (Table 6). In SCC, CLEC3B expression was positively correlated with majority of gene markers of different functional T cells (CD8+ T, Th1, Th2, etc.…”
Section: Clec3b Expression Is Associated With Immune Infiltration Inmentioning
confidence: 99%
“…Tumor-infiltrating immune cells play an important role in promoting or inhibiting tumor growth. As an integral part of the tumor microenvironment, tumor-infiltrating immune cells exist in all stages of cancer and play a vital role in shaping the development of tumors 54 . To study the effect of immune cell infiltration on the tumor microenvironment on the prognosis of LUAD patients, we used the TIMER to calculate the extent of infiltrations of CD4 + T cells, CD8 + T cells, B cells, neutrophils, macrophages, and dendritic cells and correlated the data with the expression of the identified crucial prognostic genes.…”
Section: Discussionmentioning
confidence: 99%